Fikih sebagai landasan harmoni antar umat beragama di Indonesia - Hikam, Muhammad Izzatul (Maliki Interdisciplinary Journal, 2024)
This article discusses the important role of fiqh in maintaining harmony between religious communities in Indonesia, a country rich in religious diversity. With Islam as the majority, Indonesia reflects religious diversity in various aspects of daily life. Fiqh, as a branch of knowledge in Islam, provides guidelines on how to carry out religious teachings, including the principles of tolerance, justice and respect for individual rights. Through a deep understanding of the principles of fiqh, Muslims can play an important role in strengthening social harmony and maintaining peace between religious communities. This article explores how the principles of fiqh, when applied in everyday life, can become the foundation for building good relations between Muslims and other religious communities. Thus, this article not only broadens understanding of Islamic law, but also inspires the importance of inter-religious harmony in a pluralist society. Through a deep understanding of the principles of fiqh, Indonesian society can continue to be an example of how religious diversity can be a source of strength and harmony. By respecting differences and promoting universal values of justice and compassion, Indonesia can shape a brighter future for all its citizens.